2015
DOI: 10.1002/advs.201500070
|View full text |Cite
|
Sign up to set email alerts
|

Phases Hybriding and Hierarchical Structuring of Mesoporous TiO2 Nanowire Bundles for High‐Rate and High‐Capacity Lithium Batteries

Abstract: A hierarchical mesoporous TiO2 nanowire bundles (HM‐TiO2‐NB) superstructure with amorphous surface and straight nanochannels has been designed and synthesized through a templating method at a low temperature under acidic and wet conditions. The obtained HM‐TiO2‐NB superstructure demonstrates high reversible capacity, excellent cycling performance, and superior rate capability. Most importantly, a self‐improving phenomenon of Li+ insertion capability based on two simultaneous effects, the crystallization of amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…TiO 2 /C-500 retains 47.9 % of capacity at 5 C, which is higher than reported anode materials based on hierarchically structured TiO 2 . 16,32 Reducing the current rate to 0.2 C results in a discharge capacity of 179 mA h g -1…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 /C-500 retains 47.9 % of capacity at 5 C, which is higher than reported anode materials based on hierarchically structured TiO 2 . 16,32 Reducing the current rate to 0.2 C results in a discharge capacity of 179 mA h g -1…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, it should be noted that the acidic condition provided by a certain amount of HCl plays a key role for effectively controlling the hydrolysis rate of TiOSO 4 during the process. [31] Without addition of HCl, we can only obtain the TiO 2 nanoparticles as shown in SEM images and the corresponding EDX patterns of the samples are displayed in Fig. 2.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…[1a] Among them, the use of porous TiO 2 has been proven to be effective for the improvement in kinetics of lithium‐ion (Li + ) insertion/extraction since the pore structure provides materials with rapid ion transport paths and a large surface area for charge transfer reactions. [5a,9] Also, it has been found that a mesoporous nanowire bundle structure could decrease the polarization and enhance performance at high rates . Modification of the material composition by doping or introduction of carbon has also been shown to enhance electrical conductivity, and thus high‐rate LIB performance, but here the focus will be on enhancing the performance of the nanoporous TiO 2 platform itself.…”
Section: Introductionmentioning
confidence: 99%